I'm currently trying to solve the following:

(∃x(¬A(x))) → [∀x (A(x)) → B(z) ]

using only the rules of predicate and propositional calculus. I've had a few stabs at the problem. My chief idea has to do with the A(x) statements. I understand that if there exists at least one false A(x), then A(x) is not all true. I understand that falsities can imply anything. How do I join these two ideas together with the proper formal logical notation?

For example, I first assume:


which means:

    [∀x    (A(x)) → B(z)   ]           (=> E)
        [∀x    (A(x))]              (assume)
        A(a)                        (∀E)

So I have proved it's false. Now what?

I realise that there is a very good chance I am barking up the wrong tree but I cannot see any other way to prove this. B(z) is totally unrelated to A(z) and while existential elimination will let me arrive at a "q" statement, I do not see how I can get "q" from the other two terms.

  • $\begingroup$ About your title: a term cannot be false (nor true). Only sentences can be true or false. In fact you want a way to prove that a contradiction, e.g. the appearance of both $A(t)$ and $\lnot A(t)$ in the proof of the sentence that you mention in your post, implies any sentence. $\endgroup$ – orient Aug 24 '17 at 10:39

You're being a bit inconsistent with parenthesis in the statement you're trying to prove, and maybe your notation is a bit unclear. But the idea is correct.

What you're basically relying on is the DeMorgan theorem for quantifiers, that is the fact that $\exists x(\neg\phi(x)) \leftrightarrow \neg\forall x(\phi(x))$. The proof may be a bit difficult to word in a natural way since we're doing a conditional proof twice and also in doing that we're throwing in an assumption that we're using in RAA.

In addition it might seem a bit odd too that we assume something that directly contradicts what we're already have assumed, but that's perfectly allowed.

If we write it using symbols instead it may be a bit more "clear":

$$\begin{align} \tag{1}\exists x(\neg A(x)), \forall x(A(x))&\vdash \exists x(\neg A(x)) &\text{ Assumption}\\ \tag{2}\exists x(\neg A(x)), \forall x(A(x))&\vdash \neg\forall x(A(x)) &\text{ Assumption}\\ \tag{3}\exists x(\neg A(x)), \forall x(A(x))&\vdash \forall x(A(x)) &\text{ DeMorgan(1)}\\ \tag{4}\exists x(\neg A(x)), \forall x(A(x))&\vdash B(z) &\text{ RAA(2,3)}\\ \tag{5}\exists x(\neg A(x))&\vdash\forall x(A(x)) \rightarrow B(z) &\text{ Cond(4)}\\ \tag{6}&\vdash \exists x(\neg A(x)) \rightarrow (\forall x(A(x) \rightarrow B(z)) &\text{ Cond(5)} \end{align}$$

To be clear here, in formal logic we're not concerned with statements being true or false, we're concerned with statements being proved (possibly under a set of conditions to the left of $\vdash$ symbol). What RAA then is about is that if we have proven $\phi$ and $\neg\phi$ we can conclude $\psi$.

  • $\begingroup$ Thank you for the help. Im sorry but i dont follow. You've proved 2 different things from the same inputs in lines 2 and 3. I also don't know what RAA is. $\endgroup$ – Fuzzy Wuzzy Aug 24 '17 at 6:55
  • $\begingroup$ @FuzzyWuzzy Acronym for Reductio Ad Absurdum (ie proof by contradiction). $\endgroup$ – skyking Aug 24 '17 at 7:01

Here is a natural deduction proof (somehow informally stated). The details of the proof may vary according to how exactly your proof system is stated, but the following derivation should offer a good blueprint for adapting it to various proof systems.

The goal is to prove: $(\,\exists x\ \lnot A(x)\,)\ \to\ [ \,(\forall x\ A(x))\to B(z) \,]$.

1) Assume $\exists x\ \lnot A(x)$.

Now the goal is to prove: $(\forall x\ A(x))\to B(z)$ from assumption 1).

2) Assume $\forall x\ A(x)$.

Now the goal is to prove: $B(z)$ from assumptions 1) and 2).

3) From 1), by instantiation of a existentially quantified formula, you get: $\lnot A(t)$, where $t$ is a term not appearing in the proof so far.

4) From 2), by instantiation of a universally quantified formula, you get $A(t)$.

5) From 4), by inserting a disjunction, you get $A(t)\lor B(z)$.

6) From 3) and 5), by "disjunctive syllogism", you get $B(z)$.

Now you discharge the assumption and you get the desired result, i.e.

7) By discharging assumption 2), you get: $(\forall x\ A(x))\to B(z)$.

8) By discharging assumption 1), you get: $(\,\exists x\ \lnot A(x)\,)\ \to\ [ \,(\forall x\ A(x))\to B(z) \,]$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.